"It's a terrible way to go to work:" what 70 million readers' comments on the Guardian revealed about hostility to women and minorities online - Gardiner, Becky (Feminist media studies, 2018)
In 2006, the Guardian opened many of its articles to readers' comments to encourage a "conversation" between journalists and their readers. Readers responded enthusiastically, and by 2016 they had posted 70 million comments on the site. However, from the outset many journalists complained about the quality and tone of comments. Female and BAME (Black, Asian and minority ethnic) journalists in particular complained that they were subject to more abuse than their male, white counterparts. This study finds prima facie evidence to support the journalists' claims. Using comments that had been blocked by moderators as a proxy for abuse and dismissive trolling, it was found that articles written by women did attract a higher percentage of blocked comments than those written by men, regardless of the subject of the article; this effect was heightened when the articles ran in a particularly male-dominated section of the site. There was also evidence that articles written by BAME writers attracted disproportionate levels of blocked comments, even though the research was not designed to reveal this. Preliminary research findings were published in the Guardian and readers were invited to comment on them. Guardian journalists' experiences of comments were also surveyed. Both sets of responses are analysed here, in order to explore the contested nature of online abuse in an online news media environment, and to evaluate the potential of comments to "democratise" journalism.